2003
DOI: 10.1080/110241598750005679
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between preoperative assessment of organ function and postoperative morbidity in patients with oesophageal cancer

Abstract: Accurate preoperative assessment of pulmonary function is a valuable indicator of postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 8 publications
1
27
1
2
Order By: Relevance
“…6 Accurate preoperative staging, particularly with regard to the depth of tumor invasion, involvement of lymph nodes, and distant metastasis, is vital in determining the most appropriate procedures for curative surgery of thoracic esophageal SCC. 1 In this study, FDG uptake in the primary tumor was detected in 25 of 32 cases, and when the depth of invasion reached the propria muscle layer, FDG uptake was observed in all cases. There was significant correlation between FDG uptake and the depth of invasion, lymph node metastasis, lymphatic invasion, and the size of the tumor.…”
Section: Discussionsupporting
confidence: 47%
“…6 Accurate preoperative staging, particularly with regard to the depth of tumor invasion, involvement of lymph nodes, and distant metastasis, is vital in determining the most appropriate procedures for curative surgery of thoracic esophageal SCC. 1 In this study, FDG uptake in the primary tumor was detected in 25 of 32 cases, and when the depth of invasion reached the propria muscle layer, FDG uptake was observed in all cases. There was significant correlation between FDG uptake and the depth of invasion, lymph node metastasis, lymphatic invasion, and the size of the tumor.…”
Section: Discussionsupporting
confidence: 47%
“…In general, a poor pulmonary status involving a %VC of <80% and an FEV1.0% of <70% is associated with both pulmonary and non-pulmonary postoperative morbidity (15). In the present study, FEV1.0% was the most effective predictor of postoperative pulmonary complications, whereas %VC was not an effective predictor of postoperative pulmonary complications.…”
Section: Discussioncontrasting
confidence: 47%
“…Barrera et al evaluated 300 patients who had undergone thoracic surgery and divided them into 4 groups: non-smokers, past quitters (who stopped smoking >2 months ago), recent quitters (who stopped >1 week ago and ≤2months ago) and current smokers (31). The incidence of postoperative pneumonia was significantly different between the non-smokers and the smokers in the 4 groups, (3,10,15, and 23%, respectively). In the present study, we were not able to analyze the duration of smoking cessation in detail due to insufficient smoking data.…”
Section: Variablesmentioning
confidence: 86%
See 1 more Smart Citation
“…In the measurements, BI and blood loss had a higher tendency in the NMDT group than in the MDT group. It is reported that age, sex, and BI were considered as predictors of PPCs [21][22][23][24] . In this study, age, sex, BI, blood loss, and presence of recurrent laryngeal nerve palsy were selected as predictors of PPCs according to the previous studies.…”
Section: Resultsmentioning
confidence: 99%